Class, Ethnicity, and Immigration in Sweden: Two Films, Two Strategies. Issue 4 (December 2013) - Lindvall, Daniel
<x xml:space="preserve">Abstract</x> Against a background of growing inequality, "class" as a subject has made its comeback in Swedish arts and public debate generally. This has resulted in some very strong cinematic depictions of the upper social classes. But when it comes to the working class, films have tended to demonize or mock, to focus on criminality and drug abuse, and to equate the working class either with the immigrant population or with ethnically Swedish "rednecks" isolated from urban "civilization." Recently, however, two films have stood out by avoiding such "othering" stereotypes: Sebbe (2010) and Eat Sleep Die (2012). Both films were written and directed by filmmakers with an immigrant background: Iranian‐born Babak Najafi and Gabriella Pichler, whose Bosnian mother and Austrian father both arrived as migrant workers in the 1970s. Interestingly, the directors have chosen radically different approaches to the issue of the class–ethnicity relationship. Najafi focuses entirely on ethnically Swedish protagonists in Sweden's second largest city, Gothenburg, while Pichler situated her film among the ethnically mixed working class of a small industrial countryside town, giving her main protagonist a background similar to her own. This essay will comparatively analyze the two films against a background of contemporary Swedish history, while also highlighting how the immigrant and class experiences of the directors have beneficially influenced their work.